2016
DOI: 10.1016/j.jiph.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in critically ill patients is associated with increased need of mechanical ventilation but not with mortality

Abstract: Worldwide incidence of obesity is increasing and impaired outcome in postoperative patients has been described. Antibiotic prescribing is complicated by different pharmacology in this population. This study evaluates mortality and morbidity of obese postoperative patients and explores possible relation to antibiotic therapy. Therefore, data obtained in a prospective study in 2009-2010 were analysed. Postoperative patients on 5 ICUs were included with >48h of ICU treatment and documented body-mass-index (BMI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
4
16
0
1
Order By: Relevance
“…Malnutrition, obesity, and being overweight have been associated with poor outcomes among critically ill adult patients. 26,27 However, Goh et al reported that obesity and being overweight were not associated with mortality or morbidity among critically ill children, in line with our findings. 28 Therefore, further large-scale studies are needed to clarify the impact of being overweight on clinical outcomes among acutely critically ill children.…”
Section: Discussionsupporting
confidence: 92%
“…Malnutrition, obesity, and being overweight have been associated with poor outcomes among critically ill adult patients. 26,27 However, Goh et al reported that obesity and being overweight were not associated with mortality or morbidity among critically ill children, in line with our findings. 28 Therefore, further large-scale studies are needed to clarify the impact of being overweight on clinical outcomes among acutely critically ill children.…”
Section: Discussionsupporting
confidence: 92%
“…Vancomycin TDM showed that underdosing and overdosing occur more often and effective levels are less often achieved, in obese patients. TDM might be of special importance, in obese patients . The majority of these patients present subtherapeutic concentrations, which increases the risk of treatment failure and bacterial resistance.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…TDM might be of special importance, in obese patients. 70 The majority of these patients present subtherapeutic concentrations, which increases the risk of treatment failure and bacterial resistance.…”
Section: Obese Patientsmentioning
confidence: 99%
“…Moreover, adipose tissue accumulation in the thoracic cavity and abdomen alters respiratory physiology causing an increased load on the respiratory musculature, leading to decreased chest wall compliance and increased resistance, altered ventilation perfusion relation, lung volume, and capacity [ 5 7 ]. Recent data indicate that in intensive care units, approximately 20% of patients are obese or severely obese [ 8 ]. These patients have more complications and need longer hospitalization and mechanical ventilation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%